Thermoplastics pipe and ?tting systems for hot and cold water for domestic purposes and heating installations in buildings. Speciﬁcation for polybutylene (PB) pipe and associated ﬁttings Part 2, (28th April 2023) - British Standards Institution,
No abstract available